Humanitarian architecture and the creation of schools for disadvantaged communities in China - Du, Hang (2022)
In the past few decades, there has been increasing global concern for people in developing countries who are suffering from disasters, diseases, poverty, etc. As a result, many charitable organizations, architects, universities, and others have become involved in humanitarian projects to help alleviate these social problems by utilizing architectural design skills. Humanitarian architecture provides solutions in response to natural- and man-made societal or environmental problems and its scope can be broadly classified into two categories: ‘post-disaster’ and ‘socio-economic community development’ projects. Significantly, in recent years there have been also increasing concerns about the roles and responsibilities of architects and the appropriateness of humanitarian architecture. Similar to the global picture, research into post-disaster humanitarian architecture in China has increased significantly in recent years, however, research into ‘non-disaster relief’ projects focused on socio-economic development is rare.